2010
DOI: 10.9755/ejfa.v22i4.4877
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of different sources of nitrogen on digestible nutrient intake, nitrogen balance and production of rumen metabolites in growing Yankasa sheep

Abstract: A study was conducted to evaluate digestible nutrient intake, nitrogen balance and rumen metabolites in twenty growing Yankasa rams fed urea and /or sundried broiler litter (SDBL) as a partial or complete replacement for cotton seed cake (CSC) in diets for 90 days. The diets were: 1(CSC; control), 2(urea), 3(urea/SDBL), 4(CSC/urea) and 5(CSC/SDBL). The results indicated difference (P<0.05) in DM intake across diets, with animals fed CSC, urea and CSC/urea having the highest values (543.1, 523.4 and 483.6 g/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The higher TVFA values of 129.14 and 130.54 mmol/L recorded in this study were higher than 15.33 mmol/dl reported Jokthan by et al (2013) and 13.10 mmol/dl recorded for Yankasa rams fed with sun dried broiler litter (SDBL) (Abubakar et al, 2010). It was also higher than the range of 6.19 to 11.59 mmol/dl reported by (Ngele, 2008) and 14.02 to 15.67mmol/dl by (Elemam et al, 2009).…”
Section: Rumen Metabolites Of Growing Yankasa Rams Fed Diets Containi...contrasting
confidence: 66%
See 1 more Smart Citation
“…The higher TVFA values of 129.14 and 130.54 mmol/L recorded in this study were higher than 15.33 mmol/dl reported Jokthan by et al (2013) and 13.10 mmol/dl recorded for Yankasa rams fed with sun dried broiler litter (SDBL) (Abubakar et al, 2010). It was also higher than the range of 6.19 to 11.59 mmol/dl reported by (Ngele, 2008) and 14.02 to 15.67mmol/dl by (Elemam et al, 2009).…”
Section: Rumen Metabolites Of Growing Yankasa Rams Fed Diets Containi...contrasting
confidence: 66%
“…Rumen liquor was collected in the morning (0 hour before feeding) and (4 hours after feeding) at the last week of the experiment with a suction tube as describe by Abubakar et al (2010). The tube was inserted from the mouth into the rumen where 20mls of rumen liquor was withdrawn from three (3) animals in each treatment.…”
Section: Rumen Fluid Collectionmentioning
confidence: 99%
“…Ruminal ammonia concentration resulted in present research varied from 11.50 to 15.00 mM (equivalent with 161 to 210 mg ammonia N/L) and fallen within ruminal ammonia N range (12.48 to 18.28 mM, with optimal level of 13.78 mM) of young rams fed rations contained different level of hydrolyzed feather meal as reported by Puastuti and Mathius (2008). Moreover, Abubakar et al (2010) reported higher ruminal ammonia N concentrations, i.e. in range of 21.5 to 37.5 mg/100 ml (about 15.36 to 26.79 mM) resulted from sheep fed rations contained different nitrogen sources.…”
Section: Ruminal Ammoniamentioning
confidence: 96%
“…This is an indication that there was no kidney dysfunction or the diets provided adequate protein for the animals (Aruwayo, et al, 2011). The higher values of blood urea nitrogen for rams receiving UGNS diets in this study might be as a result of high release of ammonia in the rumen resulting to high absorption of ammonia from the rumen into the blood (Abubakar et al, 2010;Gunun et al, 2013b;Nayawo et al, 2017). Also, Yadav and Yadav (1988) reported increased in blood urea in cattle fed treated straw compared to the untreated.…”
Section: Serum Biochemical Parameters In Yankasa Rams Fed Experimentamentioning
confidence: 70%